Sorption-spectrophotometric method for the determination of Pd(II) in aqueous solutions - Vasić Vesna M.; Savić Jasmina Z.; Vukelić Nikola S. (Journal of the Serbian Chemical Society, 2004)
The reaction of Pd(II) with 1,8-dihydroxy-2-(pyrazol-5-ylazo)-naphthalene 3-6-disulphonic acid (PACA) sorbed onto Dowex 1-X8 ion-exchange resin was investigated with the aim of developing an absorption-spectrophotometric analytical method for the determination of low Pd(II) concentrations in water. The immobilized reagent formed a 1:1 complex with Pd(II) having an absorption maximum at 650 nm. Parameters, such as pH, wavelength and contact time were optimised for a given amount of the sorbed reagent. The linearity range of absorbance vs. Pd(II) concentration extended from 5x10-6 – 5x10-5 M 5x10-7 – 5x10-6 and 2.5x10-8 – 2.5x10-7 M when using 10, 100 and 200 ml of sample solution, respectively. With a 200 ml sample, the detection limit was 2.5x10-7 M Pd(II). Most metals, except Cu(II), did not interfere when present in up to 100 times the concentration of Pd(II).